PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO ANIMASI UNTUK MENINGKATKAN KEMAMPUAN BERHITUNG SISWA KELAS II SEKOLAH DASAR - Rizqi Esa Nurkhafid; Anita Chandra Dewi Sagala; Singgih Adhi Prasetyo (STKIP Subang, 2023)
The background to the problem in this research is how to develop animated video learning media to improve the numeracy skills of class II elementary school students? And is it considered appropriate to use animated video learning media to improve students' numeracy skills? So the goal to be achieved in this research is to increase the numeracy skills of class II elementary school students through learning media in the form of animated videos. This type of research is research and development using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. The media in this development research must go through assessment subjects in the form of media expert validation, material experts, teacher response questionnaires, and student response questionnaires in order to strengthen media validation. The results of the development are animated video learning media to improve students' numeracy skills. Animated video media was declared valid as proven by validation results by learning media experts of 64%, validation by material experts of 88%. The animated video learning media was also stated to be practical as proven by the results of teacher responses of 90% and student responses of 100%. The level of effectiveness of the media on class II students' numeracy skills shows an increase in the post-test results which have been tested using the T-test.